Study on carbon nano-tube spun thread as piezoresistive sensor element - Mallik N.; Schulz M.J.; Shanov V.N.; Hurd D.; Chakraborty S.; Jayasinghe C.; Abot J.; Song A. (My University, 2025)
Carbon nanotube spun threads are becoming growingly important for various technological and medical applications. Threads can be spun directly from carbon nanotube arrays using age old method of spinning. The process involves two rotations about two mutually perpendicular axes viz. spinning nanotubes into thread from array and winding the spun thread on spool. It is found that an array with properties of high uniform density, low amorphous carbon content and highly aligned nano-tubes are better spinnable. Piezoresistive property of spun thread is investigated through experiments. The change in resistivity of spun carbon nanotube thread with change in load will enable its use as force sensors. In a structural neural network system a network of sensors can pinpoint the location of damage in structure. If such network can be made of very small dimension it can detect crack initiation and crack propagation. Linearity of resistivity increase with increase in strain is observed for fine spun carbon nanotube threads. Upon unloading also this linearity is preserved with same slope. © (2009) Trans Tech Publications.